(untitled) (World Science, 2018)
The paper considers the influence of the vibrational load on the deformation of soils with an increased moisture content. In the course of theoretical studies, it was established that the effect of vibration on soil deformation is observed when vibrational accelerations of a strictly defined limiting value are reached, which is usually called critical. It is established that the dependence of the critical acceleration on the specific static pressure is parabolic. In this case, the influence of vibration on the deformation of the soil is well described by the hyperbola equation. The presence of a limit of the sensitivity of the soil to vibrations is established, at the attainment of which a complete destruction of the cohesion forces is observed, which are not restored, and the internal friction reaches a maximum determined by the physical and mechanical characteristics of the soil. It is determined that the vibrations caused by the force in the vertical plane do not have a noticeable effect on the shear resistance. If the vector of the perturbing force coincides with the plane of shear, then the tangential stresses form an exponential dependence.